Silicon-based negative electrode material aqueous slurry composition, and preparation method and application thereof

CN117133874BActive Publication Date: 2026-10-30TOMI CHENGDU APPLIED TECH RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210554112.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-20
Publication Date
2026-10-30
Estimated Expiration
2042-05-20

AI Technical Summary

Technical Problem

这种高分散转速(超过20m/s的线速度)会将长度超过100μm的硅纳米线打断成20μm以下的颗粒,失去硅纳米线的长度优势;

Benefits of technology

[0070]本发明提供了一种制备硅基负极材料水性浆料组合物的方法,通过预先将硅基负极材料用化学分散剂,降低硅基负极材料的表面活性能,进而利于硅基负极材料相互之间的分散;再通过抽真空去除蓬松的硅基负极材料中的空气,利于溶剂与分散剂充分浸润硅基负极材料;然后在真空状态下,通过搅拌头和分散头的自转和公转,全方位、无死角地给予硅纳米线团机械碰撞、剪切力。通过控制转速来控制搅拌头和分散头的线速度,控制其对硅基负极材料的结构(主要是长度)破坏,在较低的转速下,能够保留硅基负极材料的结构,又能将硅基负极材料分散成均匀分散的浆料;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117133874B_ABST
    Figure CN117133874B_ABST
Patent Text Reader

Abstract

The application provides a silicon-based negative material aqueous slurry composition and a preparation method and application thereof. The method comprises the following steps: (1) mixing a dispersant A and a solvent to form a dispersant A solution, and then adding a silicon-based negative material to perform vacuum low-speed stirring to obtain a silicon-based negative material pre-dispersion liquid; (2) mixing a thickening agent and a solvent, performing vacuum stirring to disperse to form a thickening agent solution, and then adding a dispersant B and a conductive agent to perform vacuum high-speed stirring to obtain a conductive glue solution; (3) mixing the silicon-based negative material pre-dispersion liquid obtained in the step (1) and the conductive glue solution obtained in the step (2), and then performing vacuum low-speed stirring, adding a binder and a defoaming agent to perform secondary vacuum low-speed stirring to obtain the silicon-based negative material aqueous slurry composition. The application adopts a chemical dispersion and mechanical dispersion combined mode to prepare the uniform and stable silicon-based negative material aqueous slurry composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of anode material technology, specifically relating to an aqueous slurry composition of silicon-based anode material, its preparation method, and its application. Background Technology

[0002] In recent years, the new energy industry has developed rapidly, and the demand for lithium-ion batteries has grown rapidly. The market has placed higher demands on the energy density, low-temperature performance, fast-charging performance, safety performance, and manufacturing cost of lithium-ion batteries. Silicon nanowires, as a lithium-ion battery anode material, have a theoretical electrochemical capacity of 4199 mAh / g, and their energy density is ten times that of graphite-based anode materials. Silicon materials have a lower charge / discharge voltage plateau, with a lithium potential of 0.5V, making them less prone to surface lithium deposition, and their safety performance is superior to graphite materials. Compared with silicon nanoparticles, silicon nanowires exhibit less macroscopic expansion during charge and discharge, resulting in a longer battery cycle life. Therefore, silicon nanowires are considered a viable alternative to graphite-based anode materials for lithium-ion batteries and have significant application value.

[0003] Currently produced silicon nanowires are generally over 100 μm in length and are intertwined, forming very loose, flocculent clumps with a specific surface area exceeding 200 m². 2 / g. Conventional lithium-ion battery anode slurry mixing techniques can lead to silicon nanowire breakage, difficulty in obtaining slurries with high solids content, and difficulty in uniformly dispersing silicon nanowires. Lithium-ion battery anode slurries are typically prepared using aqueous mixing techniques. The slurry consists of an active material (graphite or silicon-carbon anode, etc.), conductive agent, binder, thickener, defoamer, and deionized water. A fully dispersed and stable anode slurry is obtained through homogenization.

[0004] There are two main types of lithium-ion battery negative electrode slurry mixing technologies: one is the wet slurry mixing technology, which involves first dissolving a thickener or water-based binder with about 90% solvent to prepare a slurry, then adding a conductive agent to the slurry for dispersion, then adding the main material graphite or silicon-carbon negative electrode to the system, stirring evenly, adding the remaining solvent to adjust to a suitable viscosity, and finally adding the binder and defoamer to the system, dispersing the negative electrode slurry by gradually increasing the solids content; the other is the dry slurry mixing technology, which generally requires first dissolving a thickener with a portion of the solvent to prepare a high-concentration slurry, then simultaneously adding the active main material and conductive agent to the prepared slurry, stirring and kneading at high viscosity, and then adding the remaining solvent, binder and defoamer to the system and mixing evenly, dispersing the negative electrode slurry by gradually decreasing the solids content.

[0005] However, if silicon nanowire materials are produced using traditional negative electrode slurry technology, the following three problems will arise:

[0006] (1) High-speed shearing leads to the breakage of silicon nanowires. Both dry and wet slurry mixing techniques employ strong shearing forces at high dispersion speeds (generally exceeding 20 m / s) at the end of the mixing process to break up agglomerated particles and obtain a uniformly dispersed slurry. This high dispersion speed (linear velocity exceeding 20 m / s) breaks silicon nanowires longer than 100 μm into particles shorter than 20 μm, thus negating the length advantage of silicon nanowires.

[0007] (2) High viscosity kneading leads to silicon nanowire breakage. In the early stage of slurry mixing, the dry slurry mixing technology uses high viscosity and low speed stirring to disperse agglomerated particles by utilizing the strong internal friction between materials. This does not cause the material structure to be destroyed. However, the strong internal friction will cause the silicon nanowires to break into silicon particles, thus losing the length advantage of the nanowires.

[0008] (3) Silicon nanofibrillated clumps cannot be dispersed evenly, resulting in a large number of coarse particles with a diameter exceeding 50 μm. Because silicon nanowires are intertwined into loose clumps, regardless of whether dry or wet slurry mixing technology is used, the high viscosity internal friction or high-speed shear force cannot completely break up these clumps, allowing the conductive agent and binder to mix fully and evenly. The dispersed slurry contains a large number of coarse particles with a diameter exceeding 50 μm, which cannot meet the subsequent coating quality requirements.

[0009] Therefore, in order to address the aforementioned problems, it is desirable to develop an aqueous slurry composition and preparation method for silicon-based anode materials to solve these problems, thereby improving the electrochemical performance of the battery while maintaining good cycle performance. Summary of the Invention

[0010] To address the shortcomings of existing technologies, the present invention aims to provide an aqueous slurry composition for silicon-based anode materials, its preparation method, and its applications. The present invention employs a combination of chemical and mechanical dispersion methods. First, the silicon-based anode material is pre-dispersed into a uniform and stable dispersion, while a thickener and a conductive agent are dispersed into a uniform conductive adhesive. Then, the two are mechanically mixed and dispersed, and a binder and defoamer are added and dispersed uniformly to obtain a uniform and stable aqueous slurry composition for silicon-based anode materials.

[0011] To achieve this objective, the present invention adopts the following technical solution:

[0012] In a first aspect, the present invention provides a method for preparing an aqueous slurry composition for silicon-based anode materials, the method comprising the following steps:

[0013] (1) Dispersant A and solvent are mixed to form a dispersant A solution, and then silicon-based anode material is added and stirred at low speed under vacuum to obtain a silicon-based anode material pre-dispersion liquid;

[0014] (2) Mix the thickener and solvent, disperse them under vacuum to form a thickener solution, then add dispersant B and conductive agent and stir under vacuum at high speed to obtain a conductive adhesive solution;

[0015] (3) The silicon-based anode material pre-dispersion liquid obtained in step (1) and the conductive adhesive liquid obtained in step (2) are mixed, and then vacuum low-speed stirring is performed. A binder and defoamer are added and vacuum low-speed stirring is performed again to obtain the silicon-based anode material aqueous slurry composition.

[0016] This invention pre-disperses a difficult-to-disperse silicon-based anode material under vacuum and low-speed conditions with the addition of a suitable dispersant A, resulting in a silicon-based anode material pre-dispersion with well-preserved structure. The difficult-to-disperse silicon-based anode material is then mixed with a conductive agent and a thickener, and pre-dispersed under vacuum and high-speed conditions with the addition of a suitable dispersant B, resulting in a conductive colloid with excellent conductivity. Finally, the two uniformly dispersed slurry systems are mechanically mixed to form a homogeneous slurry system. This invention perfectly solves the problem of using different dispersants for silicon-based anode materials and conductive colloids, avoiding interference between the two dispersants and thus affecting the dispersion effect. It also solves the problem of the inability to simultaneously achieve the required low-speed dispersion of silicon-based anode materials and the high-speed dispersion of conductive agents, resulting in an aqueous slurry composition of silicon-based anode materials with uniform dispersion, excellent conductivity, and good cycle performance.

[0017] Preferably, the aqueous slurry composition of the silicon-based anode material comprises, by weight, 30-90 parts of silicon-based anode material, 0.1-10 parts of the total weight of dispersant A and dispersant B, 5-50 parts of conductive agent, 1-5 parts of thickener, 3-10 parts of binder, 0.5-5 parts of defoamer, and 100-500 parts of solvent.

[0018] In this invention, the silicon-based anode material is 30-90 parts, for example, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 ​​parts, 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts, 87 parts, or 90 parts.

[0019] In this invention, by adjusting the weight percentage of the silicon-based anode material, the high energy density advantage of silicon-based materials can be maintained, while ensuring that the silicon-based anode material is fully dispersed and uniformly mixed with the conductive agent and binder. If the weight percentage is too low, the high energy density advantage will be lost; if the weight percentage is too high, the silicon-based anode material will easily agglomerate into large particles that are difficult to disperse and mix uniformly with the conductive agent and binder.

[0020] In this invention, the total weight of dispersant A and dispersant B is 0.1-10 parts, for example, 0.1 parts, 0.5 parts, 0.8 parts, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, or 10 parts.

[0021] In this invention, by adjusting the total weight of dispersant A and dispersant B, the components of the slurry can be fully and uniformly mixed. If the weight is too low, the silicon-based anode material or conductive agent will be difficult to mix evenly. If the weight is too high, the proportion of active material will be reduced, thus reducing the energy density of the battery cell.

[0022] In this invention, the conductive agent is 5-50 parts, for example, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, or 50 parts.

[0023] In this invention, by adjusting the weight percentage of the conductive agent, the conductivity of the slurry can meet the charge / discharge rate requirements of the battery cell. If the percentage is too low, the conductivity will be insufficient and it will be difficult to meet the charge / discharge rate requirements. If the percentage is too high, the proportion of active material in the negative electrode material will be reduced, thereby reducing the energy density of the battery.

[0024] In this invention, the thickener is 1-5 parts, for example, 1 part, 2 parts, 3 parts, 4 parts, or 5 parts.

[0025] In this invention, by adjusting the weight percentage of the thickener, the slurry achieves a suitable viscosity, ensuring good operability during coating. Too low a percentage results in low viscosity, leading to numerous problems in subsequent coating processes, such as unstable areal density, accumulation of conductive agent on the surface, or accumulation of binder on the bottom layer. Too high a percentage results in excessive viscosity, causing difficulty in slurry flow and leading to various problems in subsequent coating processes, such as rough surfaces, coating scratches, stringing, tailing, and excessive edge thickness. Furthermore, an excessively high percentage can reduce the amount of active material, thereby lowering the battery's energy density.

[0026] In this invention, the adhesive is 3-10 parts, for example, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, or 10 parts.

[0027] In this invention, by adjusting the weight percentage of the binder, the electrode sheet can have good adhesion and suitable internal resistance. If the weight percentage is too low, the adhesion between the material and the current collector will be insufficient, which will seriously affect the performance of the battery, such as short cycle life, electrode sheet peeling, powder shedding and short circuit. If the weight percentage is too high, it will increase the internal resistance of the battery, which will seriously affect the performance of the battery, such as high internal resistance, low capacity and heat generation.

[0028] In this invention, the defoamer is 0.5-5 parts, for example, it can be 0.5 parts, 0.8 parts, 1 part, 2 parts, 3 parts, 4 parts, or 5 parts.

[0029] In this invention, by adjusting the weight percentage of the defoamer, the slurry can have good coating performance. If the weight percentage is too low, the gas content in the slurry will be high, causing many problems such as unstable electrode surface density, pores, pinholes and exposed foil during coating. If the weight percentage is too high, it will reduce the proportion of active material, resulting in a decrease in battery energy density.

[0030] In this invention, the solvent is 100-500 parts, for example, 100 parts, 120 parts, 150 parts, 180 parts, 200 parts, 220 parts, 250 parts, 270 parts, 300 parts, 320 parts, 350 parts, 370 parts, 400 parts, 420 parts, 450 parts, 480 parts, or 500 parts.

[0031] Preferably, the dispersant A in step (1) includes any one or a combination of at least two of the following: sodium carboxylate anionic surfactant, sodium sulfonate anionic surfactant, polyol nonionic surfactant, sodium phosphate anionic surfactant, amino acid amphoteric surfactant, sodium tripolyphosphate or sodium hexametaphosphate, preferably sodium carboxylate anionic surfactant.

[0032] Preferably, the weight of dispersant A in step (1) is 0.05-5 parts, for example, 0.05 parts, 0.08 parts, 0.1 parts, 0.5 parts, 0.8 parts, 1 part, 2 parts, 3 parts, 4 parts, or 5 parts.

[0033] In this invention, by adjusting the weight percentage of dispersant A, the silicon-based anode material can be fully and uniformly dispersed in the solvent to form a stable suspension. If the weight percentage is too low, the silicon-based anode material will not be fully dispersed, and the dispersed silicon-based anode material will re-aggregate during the standing process. If the weight percentage is too high, the mass ratio of the silicon-based anode material will be reduced, thus reducing the energy density of the battery. An excessively high weight percentage of dispersant may also reduce the battery's electrical performance, such as charge-discharge efficiency and cycle life.

[0034] Preferably, the mass concentration of dispersant A in the dispersant A solution in step (1) is 0.1%-10%, more preferably 1%-3%, for example, it can be 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.

[0035] In this invention, by adjusting the mass concentration of dispersant A, the dispersant can achieve the optimal proportion in the dispersion system, so that the silicon-based anode material will not settle or agglomerate during long-term standing, thus maintaining the stability of the system. If the mass concentration is too low, the silicon-based anode material will settle or agglomerate, while if it is too high, the battery energy density and electrical performance will decrease.

[0036] Preferably, the solvent in step (1) is deionized water.

[0037] Preferably, the silicon-based anode material in step (1) includes silicon nanowires or silicon nanowire powder coated with carbon.

[0038] Preferably, in step (1), the mass concentration of the silicon-based anode material in the silicon-based anode material pre-dispersion solution is 1%-50%, more preferably 10%-30%, for example, it can be 1%, 3%, 5%, 7%, 9%, 10%, 12%, 15%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 40%, 45%, or 50%.

[0039] In this invention, by adjusting the mass concentration of the silicon-based anode material, the silicon-based anode can form a uniform and stable suspension in the dispersion liquid. If the mass concentration is too low, the coating efficiency will be reduced and the coating energy consumption will be increased. Conversely, if the mass concentration is too high, agglomeration will occur or sedimentation will occur during the standing process.

[0040] Preferably, the vacuum degree of the vacuum low-speed stirring in step (1) is -0.08MPa to -0.1MPa, for example, it can be -0.08MPa, -0.082MPa, -0.085MPa, -0.087MPa, -0.09MPa, -0.092MPa, -0.095MPa, -0.097MPa, or -0.1MPa.

[0041] Preferably, the linear velocity of the stirring head of the vacuum low-speed stirring in step (1) is 1-10 m / s, and the linear velocity of the dispersing head is 1-10 m / s, for example, it can be 1 m / s, 3 m / s, 5 m / s, 7 m / s, or 10 m / s.

[0042] Preferably, the vacuum low-speed stirring time in step (1) is 2h-48h, for example, it can be 2h, 6h, 8h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, or 48h.

[0043] Preferably, the thickener in step (2) includes sodium carboxymethyl cellulose.

[0044] Preferably, the solvent in step (2) is deionized water.

[0045] Preferably, the mass concentration of the thickener solution in step (2) is 0.5%-3%, for example, it can be 0.5%, 0.8%, 1%, 2%, or 3%.

[0046] In this invention, by adjusting the mass concentration of the thickener solution, the dispersion system is made to have a suitable viscosity, so as to promote the dispersion effect and ensure the stability of the dispersion system. If the mass concentration is too low, the dispersion effect will be poor and the solids will easily settle. Conversely, if the mass concentration is too high, it will lead to an increase in the internal resistance of the battery cell and a deterioration in electrical performance.

[0047] Preferably, the vacuum degree of the vacuum stirring in step (2) is -0.08MPa to -0.1MPa, for example, it can be -0.08MPa, -0.082MPa, -0.085MPa, -0.087MPa, -0.09MPa, -0.092MPa, -0.095MPa, -0.097MPa, or -0.1MPa.

[0048] Preferably, the linear velocity of the stirring head in step (2) is 10-20 m / s, and the linear velocity of the dispersing head is 10-20 m / s, for example, it can be 10 m / s, 11 m / s, 12 m / s, 13 m / s, 14 m / s, 15 m / s, 16 m / s, 18 m / s, or 20 m / s.

[0049] Preferably, the vacuum stirring time in step (2) is 1h-3h, for example, 1h, 2h, or 3h.

[0050] Preferably, the dispersant B in step (2) is at least one of polyvinylpyrrolidone or alkylphenol polyoxyethylene ether.

[0051] Preferably, the weight of dispersant B in step (2) is 0.05-5 parts, for example, 0.05 parts, 0.08 parts, 0.1 parts, 0.5 parts, 0.8 parts, 1 part, 2 parts, 3 parts, 4 parts, or 5 parts.

[0052] In this invention, by adjusting the weight fraction of dispersant B, the carbon nanotubes in the conductive agent can be effectively dispersed and remain stable without settling during the standing process. If the fraction is too low, it will be difficult to disperse evenly and will easily agglomerate and settle during the standing process. If the fraction is too high, it will reduce the proportion of active material and lead to a decrease in energy density.

[0053] Preferably, the conductive agent in step (2) is a combination of conductive carbon black, conductive graphite and carbon nanotubes.

[0054] Preferably, the vacuum degree of the high-speed vacuum stirring in step (2) is -0.08MPa to -0.1MPa, for example, it can be -0.08MPa, -0.082MPa, -0.085MPa, -0.087MPa, -0.09MPa, -0.092MPa, -0.095MPa, -0.097MPa, or -0.1MPa.

[0055] Preferably, the linear velocity of the stirring head of the vacuum high-speed stirring in step (2) is 10-20 m / s, and the linear velocity of the dispersing head is 10-20 m / s, for example, it can be 10 m / s, 12 m / s, 15 m / s, 18 m / s, or 20 m / s.

[0056] Preferably, the vacuum high-speed stirring time in step (2) is 1h-6h, for example, 1h, 2h, 3h, 4h, 5h, or 6h.

[0057] Preferably, the vacuum degree of the vacuum low-speed stirring in step (3) is -0.08MPa to -0.1MPa, for example, it can be -0.08MPa, -0.082MPa, -0.085MPa, -0.087MPa, -0.09MPa, -0.092MPa, -0.095MPa, -0.097MPa, or -0.1MPa.

[0058] Preferably, the linear velocity of the stirring head of the vacuum low-speed stirring in step (3) is 1-10 m / s, and the linear velocity of the dispersing head is 1-10 m / s, for example, it can be 1 m / s, 3 m / s, 5 m / s, 7 m / s, 10 m / s, 12 m / s, 15 m / s, 18 m / s, or 20 m / s.

[0059] Preferably, the vacuum low-speed stirring time in step (3) is 3h-12h, for example, 3h, 6h, 8h, 10h, or 12h.

[0060] Preferably, the secondary vacuum low-speed stirring in step (3) further includes a sieving step.

[0061] Preferably, the sieving step is to pass the material through an 80-150 mesh sieve.

[0062] Preferably, the viscosity of the aqueous slurry composition of the silicon-based anode material in step (3) is 1500 mPa·s-3000 mPa·s, for example, it can be 1500 mPa·s, 1800 mPa·s, 2000 mPa·s, 2200 mPa·s, 2400 mPa·s, 2600 mPa·s, 2800 mPa·s, or 3000 mPa·s.

[0063] In this invention, by adjusting the viscosity of the aqueous slurry composition of the silicon-based anode material, the slurry has good leveling properties and stability. If the viscosity is too low, the subsequent coating density will be unstable and the coating size will be difficult to control. Conversely, if the viscosity is too high, the coated electrode surface will not be smooth and the coating density will be uneven.

[0064] Preferably, the solid content of the aqueous slurry composition of the silicon-based anode material in step (3) is 1%-50%, more preferably 10%-30%, for example, it can be 1%, 3%, 5%, 7%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, or 50%.

[0065] In this invention, by adjusting the solid content of the aqueous slurry composition of the silicon-based anode material, the silicon-based anode can be uniformly and effectively dispersed, and the slurry has a suitable viscosity. In the subsequent coating process, the composition and areal density can be stably met to meet the process requirements and reduce energy consumption. If the solid content is too low, the slurry will be layered and the areal density will be difficult to stably meet the process requirements during the coating process, and energy consumption will be increased. Conversely, if the solid content is too high, the silicon-based anode will be difficult to disperse uniformly and effectively.

[0066] In a second aspect, the present invention provides an aqueous slurry composition for silicon-based anode materials, wherein the aqueous slurry composition for silicon-based anode materials is prepared by means of the method described in the first aspect.

[0067] Thirdly, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a current collector and a negative electrode active material layer coated on the surface of the current collector, the negative electrode active material layer being prepared using the negative electrode aqueous slurry composition described in the second aspect.

[0068] Fourthly, the present invention provides an electrochemical energy storage device, the electrochemical energy storage device comprising a shell, a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the negative electrode is the negative electrode described in the third aspect.

[0069] Compared with the prior art, the present invention has the following beneficial effects:

[0070] This invention provides a method for preparing an aqueous slurry composition of silicon-based anode materials. The method involves pre-treating the silicon-based anode materials with a chemical dispersant to reduce their surface activity, thereby facilitating dispersion among the materials. Then, vacuuming removes air from the loose silicon-based anode materials, allowing the solvent and dispersant to fully wet them. Finally, under vacuum, the rotation and revolution of the stirring and dispersing heads provide omnidirectional and comprehensive mechanical collision and shearing forces to the silicon nanowires. By controlling the rotation speed, the linear velocity of the stirring and dispersing heads is controlled, minimizing damage to the structure (mainly length) of the silicon-based anode materials. At lower rotation speeds, the structure of the silicon-based anode materials can be preserved while dispersing them into a uniformly dispersed slurry.

[0071] Because silicon-based anode materials have poor conductivity, this invention employs a composite conductive additive consisting of conductive carbon black, conductive graphite, and conductive carbon nanotubes to ensure that the conductivity of the anode sheet made from the aqueous slurry of silicon-based anode material meets the rate discharge performance requirements of the power battery. Conductive carbon black and conductive graphite, as point-contact conductive agents, can fully fill the gaps in the silicon-based anode material, achieving uniform filling. However, the volume change of the silicon-based anode material exceeds 80% during charge and discharge. During this process, the contact between the particulate conductive agent and the silicon-based anode material, as well as between the conductive agents themselves, weakens. Therefore, linear carbon nanotubes are used to connect the point-like conductive agents and the silicon-based anode material, enhancing electronic conductivity and mitigating the impact of repeated volume expansion and contraction of the silicon-based anode material on its deteriorated conductivity.

[0072] Conventional dispersion processes for conductive carbon black and conductive graphite are relatively mature, but carbon nanotubes have a large specific surface area and are prone to agglomeration. Conventional high-speed mechanical dispersion methods are difficult to disperse them uniformly. Therefore, this invention uses a combination of chemical dispersants and high-speed mechanical dispersion to solve the problem of carbon nanotubes being difficult to disperse. Attached Figure Description

[0073] Figure 1 This is a flowchart of the method for preparing an aqueous slurry composition for silicon-based anode materials provided in Example 1;

[0074] Figure 2 The image shows a SEM image of the negative electrode sheet provided in Example 1, with a scale bar of 50 μm.

[0075] Figure 3 The charge-discharge curve of the lithium-ion battery provided in Application Example 1 shows lithium plating at the negative electrode at -10℃±1℃.

[0076] Figure 4 The charge-discharge curves of the lithium-ion battery provided in Application Example 1, showing no lithium plating on the negative electrode at -10℃±1℃. Detailed Implementation

[0077] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be considered as specific limitations thereof.

[0078] The sources of each component in the examples are as follows: Silicon-based anode: self-made silicon nanowires TOMI (the preparation method is detailed in patent CN112599758A, entitled "Nano-silicon Aggregate Composite Anode Material and its Preparation Method"); Dispersant A: POIZ532A Kao, Japan; Dispersant B: PVP K30 with a viscosity-average molecular weight of 45,000-58,000; Conductive agent: Super P (also known as SuperP Li) Belgian Temico, KS-6 Belgian Temico, carbon nanotubes with 5-8 layers and a diameter of 5-11 nm; Thickener: CMC 2200 Daicel, Japan; Binder: LA136D Chengdu Yindile; Defoamer: NMP Maichi Chemical.

[0079] Example 1

[0080] This embodiment provides an aqueous slurry composition for silicon nanowires, which comprises, by weight, 67 parts silicon nanowires, 3 parts dispersant A POIZ, 1 part dispersant B PVP K30, 10 parts conductive agent Super P, 5 parts conductive graphite KS-6, 5 parts carbon nanotubes, 3 parts thickener CMC, 5 parts binder LA136D, 1 part defoamer NMP, and 100 parts deionized water.

[0081] The preparation method of the silicon nanowire aqueous slurry composition is as follows: Figure 1 As shown, the details are as follows:

[0082] (1) Dispersant A and deionized water are mixed to form a dispersant A solution with a mass concentration of 3%. Then, silicon nanowires are added and vacuum low-speed stirring is carried out under a vacuum of -0.09MPa. The linear velocity of the stirring head is 2m / s, the linear velocity of the dispersing head is 5m / s, and the stirring time is 24h to obtain a silicon nanowire pre-dispersion liquid with a mass concentration of 5%;

[0083] (2) The thickener and deionized water are mixed and dispersed under vacuum at a vacuum degree of -0.092MPa to form a thickener solution. The linear velocity of the stirring head is 12m / s and the linear velocity of the dispersing head is 12m / s. The stirring time is 2h. The mass concentration of the thickener is 1.5%. Then, dispersant B, conductive agent Super P, conductive graphite and carbon nanotubes are added and vacuum high-speed stirring is carried out under a vacuum degree of -0.092MPa. The linear velocity of the stirring head is 12m / s and the linear velocity of the dispersing head is 12m / s. The stirring time is 3h to obtain conductive adhesive liquid.

[0084] (3) The silicon nanowire pre-dispersion liquid obtained in step (1) and the conductive adhesive liquid obtained in step (2) are mixed, and then vacuum low-speed stirring is performed under a vacuum degree of -0.092MPa. The linear velocity of the stirring head is 5m / s, the linear velocity of the dispersing head is 5m / s, and the stirring time is 24h. The binder and defoamer are added and vacuum low-speed stirring is performed again. After passing through an 80-mesh sieve, the silicon nanowire aqueous slurry composition is obtained, wherein the viscosity of the silicon nanowire aqueous slurry composition is 1500mPa·s and the solid content is 6.5%.

[0085] The method for preparing the negative electrode sheet is as follows:

[0086] The prepared slurry is coated onto the current collector, and the thickness of the copper foil of the current collector is 9μm. Subsequently, it is dried in an oven, rolled and cut into sheets to form the negative electrode sheet used to prepare the battery.

[0087] Figure 2 The image shows an SEM image of the negative electrode sheet provided in Example 1, which has a uniform network cross-linked porous structure on its surface.

[0088] Example 2

[0089] This embodiment provides an aqueous slurry composition for silicon nanowires, which comprises, by weight, 50 parts silicon nanowires, 2 parts dispersant A POIZ, 2 parts dispersant B PVP K30, 5 parts conductive agent Super P, 5 parts conductive graphite KS-6, 5 parts carbon nanotubes, 2 parts thickener CMC, 3 parts binder LA136D, 2 parts defoamer NMP, and 300 parts deionized water.

[0090] The preparation method of the silicon nanowire aqueous slurry composition is as follows:

[0091] (1) Dispersant A and deionized water are mixed to form a dispersant A solution with a mass concentration of 1%. Then silicon nanowires are added and vacuum low-speed stirring is carried out under a vacuum of -0.085MPa. The linear velocity of the stirring head is 5m / s, the linear velocity of the dispersing head is 5m / s, and the stirring time is 15h to obtain a silicon nanowire pre-dispersion liquid with a mass concentration of 10%;

[0092] (2) The thickener and deionized water are mixed and dispersed under vacuum at -0.085 MPa to form a thickener solution. The linear velocity of the stirring head is 12 m / s and the linear velocity of the dispersing head is 12 m / s. The stirring time is 2 h. The mass concentration of the thickener is 1%. Then, dispersant B, conductive agent Super P, conductive graphite and carbon nanotubes are added and vacuum high-speed stirring is carried out under vacuum at -0.085 MPa. The linear velocity of the stirring head is 18 m / s and the linear velocity of the dispersing head is 18 m / s. The stirring time is 2 h to obtain conductive adhesive solution.

[0093] (3) The silicon nanowire pre-dispersion liquid obtained in step (1) and the conductive adhesive liquid obtained in step (2) are mixed and vacuum low-speed stirred at a vacuum degree of -0.085MPa. The linear velocity of the stirring head is 5m / s, the linear velocity of the dispersing head is 5m / s, and the stirring time is 5h. The binder and defoamer are added and vacuum low-speed stirring is performed again. After passing through a 100-mesh sieve, the silicon nanowire aqueous slurry composition is obtained. The viscosity of the silicon nanowire aqueous slurry composition is 2000mPa·s and the solid content is 10%.

[0094] The method for preparing the negative electrode sheet is as follows:

[0095] The preparation method of the negative electrode in this embodiment is the same as that in Example 1.

[0096] Example 3

[0097] This embodiment provides an aqueous slurry composition for silicon nanowires, which comprises, by weight, 75 parts silicon nanowires, 4 parts dispersant A POIZ, 4 parts dispersant B PVP K30, 10 parts conductive agent Super P, 5 parts conductive graphite KS-6, 5 parts carbon nanotubes, 4 parts thickener CMC, 8 parts binder LA136D, 3 parts defoamer NMP, and 400 parts deionized water.

[0098] The preparation method of the silicon nanowire aqueous slurry composition is as follows:

[0099] (1) Dispersant A and deionized water are mixed to form a dispersant A solution with a mass concentration of 3%. Then, silicon nanowires are added and vacuum stirring is carried out at a vacuum degree of -0.095MPa. The linear velocity of the stirring head is 5m / s, the linear velocity of the dispersing head is 5m / s, and the stirring time is 36h to obtain a silicon nanowire pre-dispersion liquid with a mass concentration of 30%;

[0100] (2) The thickener and deionized water are mixed and dispersed under vacuum at -0.095 MPa to form a thickener solution. The linear velocity of the stirring head is 18 m / s and the linear velocity of the dispersing head is 18 m / s. The stirring time is 2 h. The mass concentration of the thickener is 2%. Then, dispersant B, conductive agent Super P, conductive graphite and carbon nanotubes are added and vacuum high-speed stirring is carried out under vacuum at -0.095 MPa. The linear velocity of the stirring head is 15 m / s and the linear velocity of the dispersing head is 15 m / s. The stirring time is 4 h to obtain a conductive adhesive solution.

[0101] (3) The silicon nanowire pre-dispersion liquid obtained in step (1) and the conductive adhesive liquid obtained in step (2) are mixed, and then vacuum low-speed stirring is performed under a vacuum degree of -0.095MPa. The linear velocity of the stirring head is 5m / s, the linear velocity of the dispersing head is 5m / s, and the stirring time is 10h. The binder and defoamer are added and vacuum low-speed stirring is performed again. After passing through a 120-mesh sieve, the silicon nanowire aqueous slurry composition is obtained, wherein the viscosity of the silicon nanowire aqueous slurry composition is 2500mPa·s and the solid content is 30%.

[0102] The method for preparing the negative electrode sheet is as follows:

[0103] The preparation method of the negative electrode in this embodiment is the same as that in Example 1.

[0104] Example 4

[0105] This embodiment provides an aqueous slurry composition for silicon nanowires, which comprises, by weight, 30 parts silicon nanowires, 1 part dispersant A POIZ, 1 part dispersant B PVP K30, 1 part conductive agent Super P, 2 parts conductive graphite KS-6, 2 parts carbon nanotubes, 1 part thickener CMC, 3 parts binder LA136D, 1 part defoamer NMP, and 100 parts deionized water.

[0106] The preparation method of the silicon nanowire aqueous slurry composition is as follows:

[0107] (1) Dispersant A and deionized water are mixed to form a dispersant A solution with a mass concentration of 0.1%. Then silicon nanowires are added and vacuum low-speed stirring is carried out under a vacuum of -0.08MPa. The linear velocity of the stirring head is 2m / s and the linear velocity of the dispersing head is 2m / s. The stirring time is 48h to obtain a silicon nanowire pre-dispersion liquid with a mass concentration of 1% of silicon nanowires.

[0108] (2) The thickener and deionized water are mixed and dispersed under vacuum at -0.08 MPa to form a thickener solution. The linear velocity of the stirring head is 10 m / s and the linear velocity of the dispersing head is 10 m / s. The stirring time is 3 h. The mass concentration of the thickener is 0.5%. Then, dispersant B, conductive agent Super P, conductive graphite and carbon nanotubes are added and vacuum high-speed stirring is carried out under vacuum at -0.08 MPa. The linear velocity of the stirring head is 2 m / s and the linear velocity of the dispersing head is 2 m / s. The stirring time is 6 h to obtain a conductive adhesive solution.

[0109] (3) The silicon nanowire pre-dispersion liquid obtained in step (1) and the conductive adhesive liquid obtained in step (2) are mixed, and then vacuum low-speed stirring is performed under a vacuum degree of -0.08MPa. The linear velocity of the stirring head is 2m / s, the linear velocity of the dispersing head is 2m / s, and the stirring time is 12h. The binder and defoamer are added and vacuum low-speed stirring is performed again. After passing through an 80-mesh sieve, the silicon nanowire aqueous slurry composition is obtained, wherein the viscosity of the silicon nanowire aqueous slurry composition is 1500mPa·s and the solid content is 3%.

[0110] The method for preparing the negative electrode sheet is as follows:

[0111] The preparation method of the negative electrode in this embodiment is the same as that in Example 1.

[0112] Example 5

[0113] This embodiment provides an aqueous slurry composition for silicon nanowires, which comprises, by weight, 90 parts silicon nanowires, 5 parts dispersant A POIZ, 5 parts dispersant B PVP K30, 20 parts conductive agent Super P, 10 parts conductive graphite KS-6, 10 parts carbon nanotubes, 5 parts thickener CMC, 10 parts binder LA136D, 5 parts defoamer NMP, and 500 parts deionized water.

[0114] The preparation method of the silicon nanowire aqueous slurry composition is as follows:

[0115] (1) Dispersant A and deionized water are mixed to form a dispersant A solution with a mass concentration of 10%. Then, silicon nanowires are added and vacuum low-speed stirring is carried out under a vacuum of -0.1MPa. The linear velocity of the stirring head is 9m / s, the linear velocity of the dispersing head is 9m / s, and the stirring time is 3h to obtain a silicon nanowire pre-dispersion liquid with a mass concentration of 50%.

[0116] (2) The thickener and deionized water are mixed and dispersed under vacuum at -0.1MPa to form a thickener solution. The linear velocity of the stirring head is 20m / s and the linear velocity of the dispersing head is 20m / s. The stirring time is 1h. The mass concentration of the thickener is 3%. Then, dispersant B, conductive agent Super P, conductive graphite and carbon nanotubes are added and vacuum high-speed stirring is carried out under vacuum at -0.1MPa. The linear velocity of the stirring head is 20m / s and the linear velocity of the dispersing head is 20m / s. The stirring time is 1h to obtain conductive adhesive solution.

[0117] (3) The silicon nanowire pre-dispersion liquid obtained in step (1) and the conductive adhesive liquid obtained in step (2) are mixed, and then vacuum low-speed stirring is performed under a vacuum degree of -0.1MPa. The linear velocity of the stirring head is 9m / s, the linear velocity of the dispersing head is 9m / s, and the stirring time is 3h. The binder and defoamer are added and vacuum low-speed stirring is performed again. After passing through a 150-mesh sieve, the silicon nanowire aqueous slurry composition is obtained, wherein the viscosity of the silicon nanowire aqueous slurry composition is 3000mPa·s and the solid content is 50%.

[0118] The method for preparing the negative electrode sheet is as follows:

[0119] The preparation method of the negative electrode in this embodiment is the same as that in Example 1.

[0120] Example 6

[0121] The difference between this embodiment and Embodiment 1 is that the aqueous slurry composition of silicon nanowires includes 20 parts by weight of silicon nanowires, while the other components and their contents are the same as in Embodiment 1.

[0122] Example 7

[0123] The difference between this embodiment and Embodiment 1 is that the aqueous slurry composition of silicon nanowires includes 100 parts by weight of silicon nanowires, while the other components and their contents are the same as in Embodiment 1.

[0124] Example 8

[0125] The difference between this embodiment and Embodiment 1 is that the aqueous slurry composition of silicon nanowires includes 0.1 parts of dispersant A and 0.1 parts of dispersant B by weight, while the other components and their contents are the same as in Embodiment 1.

[0126] Example 9

[0127] The difference between this embodiment and Embodiment 1 is that the aqueous slurry composition of silicon nanowires includes 8 parts of dispersant A and 8 parts of dispersant B by weight, while the other components and their contents are the same as in Embodiment 1.

[0128] Example 10

[0129] The difference between this embodiment and Embodiment 1 is that the silicon nanowire aqueous slurry composition includes, by weight, 1 part of conductive agent Super P, 1 part of conductive graphite KS-6, and 1 part of carbon nanotubes. The other components and their contents are the same as in Embodiment 1.

[0130] Example 11

[0131] The difference between this embodiment and Embodiment 1 is that carbon nanotubes are not added to the conductive agent in the aqueous silicon nanowire slurry composition, while the other components and their contents are the same as in Embodiment 1.

[0132] Example 12

[0133] The difference between this embodiment and Embodiment 1 is that conductive graphite is not added to the conductive agent in the aqueous slurry composition of silicon nanowires, while the other components and their contents are the same as in Embodiment 1.

[0134] Example 13

[0135] The difference between this embodiment and Embodiment 1 is that the silicon nanowire aqueous slurry composition includes, by weight, 30 parts of conductive agent Super P, 20 parts of conductive graphite KS-6, and 10 parts of carbon nanotubes. The other components and their contents are the same as in Embodiment 1.

[0136] Example 14

[0137] The difference between this embodiment and embodiment 1 is that the mass concentration of dispersant A in the dispersant A solution in step (1) is 15%, while all other aspects are the same as in embodiment 1.

[0138] Example 15

[0139] The difference between this embodiment and Embodiment 1 is that the solid content of the silicon nanowire aqueous slurry composition in step (3) is 0.1%, while the rest is the same as in Embodiment 1.

[0140] Example 16

[0141] The difference between this embodiment and embodiment 1 is that the solid content of the silicon nanowire aqueous slurry composition in step (3) is 55%, while the rest is the same as in embodiment 1.

[0142] Comparative Example 1

[0143] Comparative Example 1 provides a negative electrode aqueous slurry composition, prepared by the following method:

[0144] The negative electrode slurry composition comprises, by weight, 70 parts silicon nanowires; 0 parts dispersant A: POIZ; 1 part dispersant B: PVPK30; 10 parts conductive agent: Super P; 5 parts conductive graphite KS-6; 5 parts carbon nanotubes; 3 parts thickener: CMC; 5 parts binder: LA136D; 1 part defoamer: NMP; and 100 parts deionized water.

[0145] The preparation method of the negative electrode sheet is the same as that in Example 1.

[0146] Comparative Example 2

[0147] This comparative example provides a negative electrode aqueous slurry composition, prepared by the following method:

[0148] The negative electrode slurry composition comprises, by weight, 67 parts silicon nanowires, 3 parts dispersant A POIZ, 1 part dispersant B PVPK30, 10 parts conductive agent Super P, 5 parts conductive graphite KS-6, 5 parts carbon nanotubes, 3 parts thickener CMC, 5 parts binder LA136D, 1 part defoamer NMP, and 100 parts deionized water.

[0149] The preparation method of the negative electrode sheet is the same as in Example 1, except that the linear velocity of the stirring head and the linear velocity of the dispersing head in step (1) are changed to the same speed parameters as in step (2): the linear velocity of the stirring head is 12 m / s, and the linear velocity of the dispersing head is 12 m / s. All other parameters are the same.

[0150] Application Examples 1 to 16 and Comparative Application Examples 1 to 2

[0151] Lithium-ion batteries were prepared using the negative electrode sheets provided in Examples 1 to 16 and Comparative Examples 1 to 2, and the preparation methods are as follows:

[0152] The fabrication of lithium-ion batteries:

[0153] (1) Coating: The prepared silicon-based anode paste is coated onto a 9μm thick copper foil, with a coating surface density of 3.5mg / cm². 2 The coating drying temperature is 90℃.

[0154] (2) Rolling: The coated electrode sheet is rolled under a pressure of 5 MPa.

[0155] (3) Sheet making: The rolled electrode sheet is punched into small pieces.

[0156] (4) Vacuum drying: The punched electrode sheets are dried at a vacuum of -0.098 MPa and a temperature of 90°C for 16 hours.

[0157] (5) Assembly: In the glove box, assemble the prepared ternary lithium positive electrode, separator, silicon carbon negative electrode and aluminum-plastic film into a 053048 soft pack battery.

[0158] (6) Drying: Dry the battery cell at a vacuum of -0.098 MPa and a temperature of 85°C for 2 hours, then purge it with 99.99% nitrogen and evacuate it to -0.098 MPa. After 30 cycles of drying, purging, and evacuation, cool it to room temperature.

[0159] (7) Electrolyte injection: Inject ternary lithium-silicon carbon negative electrode battery special electrolyte into the glove box, with an injection volume of 5g / Ah.

[0160] (8) Pre-sealing: Heat seal the liquid-filled side of the aluminum-plastic film inside the glove.

[0161] (9) Aging: The assembled batteries are aged in a 45℃ circulating oven for 24 hours.

[0162] (7) Formation: The battery is activated by charging and discharging according to the following charge and discharge regime.

[0163]

[0164] (10) Second sealing and trimming: After the cell air bag is punctured and vacuumed, it is sealed and trimmed.

[0165] Test conditions

[0166] The lithium-ion batteries prepared in Application Examples 1 to 16 and Comparative Application Examples 1 to 2 were subjected to room temperature cycling, storage performance, and cycle performance tests, respectively. The test methods are as follows:

[0167] (1) Normal temperature cycle: Cycle at 23℃±2℃ according to the following charge and discharge method.

[0168]

[0169]

[0170] (2) Storage performance: The storage performance was tested at 23℃±2℃ using the following method.

[0171]

[0172] (3) -10℃ lithium plating test: The battery was subjected to 5 charge-discharge cycles at -10℃±1℃.

[0173]

[0174] Export the battery charge / discharge cycle curve from Figures 3 to 4 Observe whether lithium plating is present.

[0175] Figure 3 and Figure 4 This indicates that constant voltage artificially limits voltage changes, while variable current introduces the influence of current on voltage. Therefore, it is impossible to analyze whether lithium plating has occurred through the charging curve. However, lithium plating can undergo subsequent reactions, and part of the lithium plating is reversible. That is, the deposited lithium metal can react in subsequent processes to generate lithium ions, which can then pass through the separator and embed into the positive electrode. The reversible reaction of lithium plating to generate lithium metal ions occurs before the extraction of lithium ions from the silicon nanowires. During discharge, if deposited lithium metal is present inside the battery, it will partially participate in the reaction, resulting in a discharge plateau on the discharge curve. When the lithium metal reaction is complete, the negative electrode potential changes to the silicon potential, causing the discharge curve to segment into two slopes. Therefore, a method is formed to determine whether lithium plating has occurred during charging by judging whether there is a reversible reaction of lithium plating on the discharge curve. (See...) Figure 3 and Figure 4 .

[0176] The test results are shown in Table 1:

[0177] Table 1

[0178]

[0179]

[0180] As can be seen from the data in Table 1, the lithium-ion batteries provided in Application Examples 1 to 5 of this invention have a capacity retention rate of 90-98% after 100 cycles at 25°C, a capacity retention rate of 92-95% for storage performance at 25°C, a capacity recovery rate of 98.7-99.8%, and no interface lithium plating phenomenon occurs at low temperatures.

[0181] This invention shows that the absence of dispersant A will lead to a significant deterioration in battery cycle performance; the use of high-speed stirring and dispersing of silicon nanowires will also result in a significant deterioration in battery cycle performance; and lithium plating will occur during low-temperature charging whether dispersant A is added or carbon nanotubes are not added.

[0182] Application Example 6 illustrates the case where the amount of silicon nanowires is too small. This will not have a significant negative impact on the battery's electrical performance, but it will reduce the battery's energy density. Application Example 9 illustrates the case where the amount of dispersant is too large. Although it can improve the degree of dispersion, it will also reduce the battery's energy density.

[0183] The applicant declares that the present invention is illustrated by the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary negative electrode material components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an aqueous slurry composition for silicon-based anode materials, characterized in that, The method includes the following steps: (1) Dispersant A and solvent are mixed to form a dispersant A solution, and then silicon-based anode material is added and stirred at low speed under vacuum to obtain a silicon-based anode material pre-dispersion liquid; (2) Mix the thickener and solvent, disperse them under vacuum to form a thickener solution, and then add dispersant B and conductive agent and stir under vacuum at high speed to obtain conductive adhesive liquid; (3) The silicon-based anode material pre-dispersion liquid obtained in step (1) and the conductive adhesive liquid obtained in step (2) are mixed, and then vacuum low-speed stirring is performed. A binder and defoamer are added and vacuum low-speed stirring is performed again to obtain the silicon-based anode material aqueous slurry composition. In step (1), the silicon-based anode material includes silicon nanowires or silicon nanowire powder coated with carbon. The dispersant A mentioned in step (1) includes any one or a combination of at least two of the following: sodium carboxylate anionic surfactant, sodium sulfonate anionic surfactant, sodium phosphate salt anionic surfactant, sodium tripolyphosphate, or sodium hexametaphosphate; The conductive agent mentioned in step (2) is a combination of conductive carbon black, conductive graphite and carbon nanotubes.

2. The method according to claim 1, characterized in that, The aqueous slurry composition of the silicon-based anode material comprises, by weight, 30-90 parts of silicon-based anode material, 0.1-10 parts of the total weight of dispersant A and dispersant B, 5-50 parts of conductive agent, 1-5 parts of thickener, 3-10 parts of binder, 0.5-5 parts of defoamer, and 100-500 parts of solvent.

3. The method according to claim 1, characterized in that, The dispersant A mentioned in step (1) is sodium carboxylate anionic surfactant.

4. The method according to claim 1, characterized in that, The weight of dispersant A in step (1) is 0.05-5 parts.

5. The method according to claim 1, characterized in that, The mass concentration of dispersant A in the dispersant A solution in step (1) is 0.1%-10%.

6. The method according to claim 5, characterized in that, The mass concentration of dispersant A in the dispersant A solution in step (1) is 1%-3%.

7. The method according to claim 1, characterized in that, The solvent mentioned in step (1) is deionized water.

8. The method according to claim 1, characterized in that, In step (1), the mass concentration of silicon-based anode material in the silicon-based anode material pre-dispersion solution is 1%-50%.

9. The method according to claim 8, characterized in that, In step (1), the mass concentration of silicon-based anode material in the silicon-based anode material pre-dispersion solution is 10%-30%.

10. The method according to claim 1, characterized in that, The vacuum degree of the vacuum low-speed stirring in step (1) is -0.08MPa to -0.1MPa.

11. The method according to claim 1, characterized in that, The linear velocity of the stirring head of the vacuum low-speed stirring described in step (1) is 1-10 m / s, and the linear velocity of the dispersing head is 1-10 m / s.

12. The method according to claim 1, characterized in that, The vacuum low-speed stirring time in step (1) is 2h-48h.

13. The method according to claim 1, characterized in that, The thickener mentioned in step (2) includes sodium carboxymethyl cellulose.

14. The method according to claim 1, characterized in that, The solvent mentioned in step (2) is deionized water.

15. The method according to claim 1, characterized in that, The mass concentration of the thickener solution in step (2) is 0.5%-3%.

16. The method according to claim 1, characterized in that, The vacuum degree of the vacuum stirring in step (2) is -0.08MPa to -0.1MPa.

17. The method according to claim 1, characterized in that, The linear velocity of the stirring head in step (2) is 10-20 m / s, and the linear velocity of the dispersing head is 10-20 m / s.

18. The method according to claim 1, characterized in that, The vacuum stirring time in step (2) is 1-3 hours.

19. The method according to claim 1, wherein the dispersant B in step (2) is at least one of polyvinylpyrrolidone or alkylphenol polyoxyethylene ether.

20. The method according to claim 1, characterized in that, The weight of dispersant B in step (2) is 0.05-5 parts.

21. The method according to claim 1, characterized in that the vacuum degree of the high-speed vacuum stirring in step (2) is -0.08MPa to -0.1MPa.

22. The method according to claim 1, characterized in that, The linear velocity of the stirring head of the vacuum high-speed stirring described in step (2) is 10-20 m / s, and the linear velocity of the dispersing head is 10-20 m / s.

23. The method according to claim 1, characterized in that, The vacuum high-speed stirring time in step (2) is 1h-6h.

24. The method according to claim 1, characterized in that, The vacuum degree of the vacuum low-speed stirring in step (3) is -0.08MPa to -0.1MPa.

25. The method according to claim 1, characterized in that, The linear velocity of the stirring head of the vacuum low-speed stirring described in step (3) is 1-10 m / s, and the linear velocity of the dispersing head is 1-10 m / s.

26. The method according to claim 1, characterized in that, The vacuum low-speed stirring time in step (3) is 3h-12h.

27. The method according to claim 1, characterized in that, The secondary vacuum low-speed stirring described in step (3) also includes a sieving step.

28. The method according to claim 27, characterized in that, The sieving step involves passing the material through an 80-150 mesh sieve.

29. The method according to claim 1, characterized in that, The viscosity of the aqueous slurry composition of silicon-based anode material in step (3) is 1500 mPa•s-3000 mPa•s.

30. The method according to claim 1, characterized in that, The solid content of the aqueous slurry composition of silicon-based anode material in step (3) is 1%-50%.

31. The method according to claim 30, characterized in that, The solid content of the aqueous slurry composition of silicon-based anode material in step (3) is 10%-30%.

32. A silicon-based anode material aqueous slurry composition, characterized in that, The aqueous slurry composition of the silicon-based anode material is prepared by the method according to any one of claims 1-31.

33. A negative electrode sheet, characterized in that, The negative electrode sheet includes a current collector and a negative electrode active material layer coated on the surface of the current collector, wherein the negative electrode active material layer is prepared using the silicon-based negative electrode material aqueous slurry composition according to claim 32.

34. An electrochemical energy storage device, characterized in that, The electrochemical energy storage device includes a shell, a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the negative electrode is the negative electrode as described in claim 33.

Citation Information

Patent Citations

  • Nano silicon aggregate composite negative electrode material and preparation method thereof

    CN112599758A

  • Dispersion method for surface non-covalent modification of nickel nanowire

    CN105642903A

  • Silicon-based active composite conductive paste applied to silicon-carbon negative electrode and negative electrode paste mixing method

    CN112186140A

  • Preparation method of silicon-based negative electrode slurry

    CN113380973A